RELATION BETWEEN pH AND THE STRONG ION DIFFERENCE (SID) IN BODY FLUIDS - Schück, Otto; Matoušovic, Karel (Biomedical papers, 2005)
Acid-base balance evaluation according to the Henderson-Hasselbalch equation enable us to assess the contribution of respiratory (pCO2) and/or non-respiratory (metabolic, HCO3-) components to the acid-base balance status. A new approach to acid-base balance evaluation according to Stewart-Fencl, which is based on a detailed physical-chemical analysis of body fluids shows that metabolic acid-base balance disorders are characterized not only by [HCO3-]. According to this concept independent variables must be taken into an account. The abnormality of concentration of one or more of the independent variable(s) determines the pH of a solution. The independent variables are: 1. strong ion difference (SID); 2. total concentration of nonvolatile weak acids [Atot]; 3. in agreement with the Henderson-Hasselbalch concept also pCO2. Traditional evaluation of acid-base balance disorders is based on the pH of body fluids (though pH may be within normal range if several acid-base balance disturbances are present). In order to maintain this view and simultaneously to respect the Stewart-Fencl principle, we invented a new equation, which uses only the independent variables to define the pH of body fluids. This analysis shows that for a given value of pCO2, the pH of body fluids is determined by a difference between SID and [Atot-]. pH = 6.1 + log((SID - [Atot-])/(0,03*pCO2)) or in itemized form: pH = 6.1 + log((([Na+] + [K+] + [Ca2+] + [Mg2+] - [Cl-] - [UA-]) - (k1[Alb] + k2[Pi]))/(0,03*pCO2)) Evaluation of the individual components of this equation enables us to detect, which of the independent variable (or a combination of independent variables) deviates from the normal range and therefore which one or ones is a cause of the acid-base balance disorder. At the end of this paper we give examples of a practical application of this equation.
Keywords: Acid-base balance/Henderson-Hasselbalch equation/Stewart-Fencl principle